Reviewing Pseudoloma neurophilia infections in the popular zebrafish model - Marta Caballero‐Huertas; Manu Soto; Laia Ribas (Reviews in Aquaculture, 2021)
Zebrafish is a worldwide used animal model to better understand cultured fish species; thus, in the last two decades, zebrafish facilities have been created in many aquaculture research centres. However, and despite the attempts of rigorous aseptic conditions for animal husbandry in wet laboratory facilities, the presence of parasites cannot be underestimated. The microsporidium Pseudoloma neurophilia , which mostly affects the central nervous system, has been listed as the most prevalent parasite in reared zebrafish. The emergence of P. neurophilia is usually detected when the individual presents irreversible morphological and/or behavioural symptoms, and consequently, the spread of the disease is inevitable, indicating that the infection is expanded across rearing tanks. This review attempts, for the first time, to collect and discuss the current information on P. neurophilia life cycle, target tissues and symptomatology of the infection occurred in zebrafish. Due to its vertical transmission together with the increasing presence of zebrafish as a model in reproduction‐related problems found in aquaculture, it is highlighted, among others, the sexual dimorphism of the pathogenic effects and the possible transgenerational implications of parasitic infections. Further, to date none effective treatments have been described, so here we provide in detail available diagnostic methods, discussing the importance of the early detection, giving safety‐rearing recommendations to decrease the presence of P. neurophilia . Our intention is to minimize parasite outbreaks in zebrafish facilities, which, on the one hand, can compromise zebrafish welfare, and on the other hand, could interfere furtively in the resulting research previously designed for improving aquaculture production but also other biomedical‐related research.